Azine- and imine-linked conjugated polyHIPEs through Schiff-base condensation reaction. Issue 4 (17th December 2021) - Kotnik, Tomaž; Žerjav, Gregor; Pintar, Albin; Žagar, Ema; Kovačič, Sebastijan
Abstract : A new alternative synthetic route to the transition-metal free π-conjugated polyHIPEs is reported, which combines the Schiff-base condensation reaction and an emulsion-templating technology. Abstract : A new alternative synthetic route to the transition-metal free π-conjugated polyHIPEs is reported, which combines the Schiff-base condensation reaction and an emulsion-templating technology. The resulting highly porous azine- or imine-linked poly(arylene) networks are characterised by high chemical resistance, thermal stability and visible-light harvesting ability. Their photocatalytic properties are investigated in the degradation of aniline dissolved in water.